(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify the task-related and non-task-related mental wandering among the students of the Kindergarten Department and the significance of the differences in the mental wandering among the students of the Kindergarten Department according to the variable of the academic stage. The research sample consisted of (400) female students from the Kindergarten Department in the College of Basic Education / Al-Mustansiriya University for the academic year 2021/2022 and to achieve the objectives of the current research, the two researchers followed the descriptive approach and built a scale to measure mental wandering based on the theory of executive control of Smallwood (Smallwood, 2013), which consists of (50) paragraphs equally divided into two areas: (Task-related, and not related to the task) and the psychometric properties (validity - reliability) of the scale were verified and the data was processed statistically. The researcher used the Statistical Package for Social Sciences program (SPSS) and the following results were reached: 1- The kindergarten students have an average level of mental wandering, and tend to the task-related domain at a higher level than the non-task-related domain. 2- It was found that there are no differences in the scale of mental wandering among the female students of the kindergarten department according to the academic stage.